The impact of nitrogen gas flushing on the stability of seasonings: volatile compounds and sensory perception of cheese & onion seasoned potato crisps. Issue 9 (10th August 2018) - Agarwal, Deepa; Mui, Lim; Aldridge, Emma; Mottram, Richard; McKinney, James; Fisk, Ian D.
Abstract : Flavoured potato crisps is the UK's most consumed snack food product. Addition of N2 gas flushing extended shelf life by 2 weeks and the addition of seasoning further enhanced the shelf life of the base crisps by 2 weeks under accelerated conditions. Abstract : The impact of natural cheese and onion seasoning on the sensory perception and shelf life stability of potato crisps was studied. This study was carried out to evaluate the impact of nitrogen (N2 ) gas flushing on the shelf-life stability and sensory attributes of cheese & onion seasoned potato crisps. Markers of lipid oxidation and flavour volatile compounds were evaluated in sliced, unwashed, batch fried potato crisps during accelerated storage at 45 °C for 10 weeks. Volatile flavour compounds were evaluated by headspace gas analysis using solid phase microextraction (SPME) GC-MS and correlated with sensory perception. Gas flushing significantly increases the shelf life of both unsalted and cheese & onion seasoned potato crisps in terms of the stability of volatile compounds and sensory perception. Further to this, the addition of the cheese & onion seasoning increased the shelf life of the base potato crisp; this is proposed to be explained by the antioxidant properties of milk proteins in the seasoning. Sensory evaluation indicated that the key negative sensory attributes reported were rancidity and stale attributes, which were correlated to the progression of lipid oxidation and loss of flavour over storage time irrespective of the packaging environment (with/without gas flushing).